2019
DOI: 10.1103/physrevlett.123.200501
|View full text |Cite
|
Sign up to set email alerts
|

Contextuality Test of the Nonclassicality of Variational Quantum Eigensolvers

Abstract: Contextuality is an indicator of non-classicality, and a resource for various quantum procedures. In this paper, we use contextuality to evaluate the variational quantum eigensolver (VQE), one of the most promising tools for near-term quantum simulation. We present an efficiently computable test to determine whether or not the objective function for a VQE procedure is contextual. We apply this test to evaluate the contextuality of experimental implementations of VQE, and determine that several, but not all, fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 83 publications
(159 reference statements)
1
38
0
Order By: Relevance
“…Then, in Sec. V we show that noncontextual Hamiltonians, defined in [41] (also studied in [42]), are reducible to commuting Hamiltonians under unitary partitioning. We close the paper with discussion and directions for future work.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Then, in Sec. V we show that noncontextual Hamiltonians, defined in [41] (also studied in [42]), are reducible to commuting Hamiltonians under unitary partitioning. We close the paper with discussion and directions for future work.…”
Section: Introductionmentioning
confidence: 91%
“…In Ref. [41], contextuality of a Pauli Hamiltonian is defined as the condition under which it is impossible to consistently assign values to the Pauli terms in the Hamiltonian. Contextuality, if present, is a manifestation of nonclassicality of the Hamiltonian.…”
Section: Noncontextual Hamiltoniansmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to its simplicity, this example has been widely used both experimentally and theoretically [ 8 , 16 , 17 , 18 , 20 , 39 , 41 ]. It was recently shown that this example is in a sense not quantum mechanical, as it lacks measurement contextuality [ 46 ]; however, the simplicity of the system makes it a good candidate for initial studies.…”
Section: Molecular Hydrogenmentioning
confidence: 99%